Qualidade de vida de sobreviventes de sepse grave após alta hospitalar: avaliação pelo EQ-5D - Contrin, Ligia Marcia (2011)
Background: Sepsis has acquired a great epidemiological importance due to its incidence in the last decade. Particularly long term outcomes are yet unknown. Sepsis continues to increase by 1.5% every year. The mortality rates from sepsis are increasingly high worldwide. The aim of this nested case-control study was to evaluate the quality of life in survivors from severe sepsis with EuroQol-5 Dimensions (EQ-5D) and “Visual Analogue Scale” (EQ-VAS). Methods. This nested case-control study was carried out in patients discharged from a tertiary teaching Hospital after been admitted in the ICU with severe sepsis. From the sepsis registry containing 349 patients, patients who survived and were discharged from the hospital were identified. Each patient with sepsis was considered as a case and the patient who was admitted immediately after was selected as a control as long as they did not have sepsis and survived ICU admission. Fifty patients from each group were eligible to take part in the study. Results: A total of 100 patients were included in the study. The patients in the sepsis group had higher mortality at 1 year (36.5%) compared to the critically ill patients without sepsis in the control group (19.7%) (RR 1.85; 1.07-3.19; p<0.05). Survivor’s mean age at hospitalization was 51.3 years in sepsis group and 52.2 years in the control group. The EQ-5D Index of the control group is 0.678 ± 0.427 in the sepsis group; 0.747 ± 0.327; (p=0.66). Older patients (>60 years old) in the sepsis group had a significantly higher prevalence of moderate to severe problems (levels 2 and 3) in all dimensions. There were no differences in EQ-VAS (79.7 ± 21.1, sepsis group and 72.7 ± 26.2, control group; p=0.19) between respondents from the both groups. A median value of 60 was obtained for septic patients older than 60 years in comparison to 88 obtained for the patients in the control group (p=0.09). Conclusion: After discharge from ICU survivors of sepsis had higher mortality rate than critically ill patients without sepsis. Older patients with sepsis had more moderate and severe problems in all dimensions evaluated for quality of life.